2016
DOI: 10.15640/ijn.v3n2a3
|View full text |Cite
|
Sign up to set email alerts
|

A Descriptive, Cross- Sectional Study Analyzing the Characteristics of an Effective Clinical Instructor: Perceptions of Baccalaureate Nursing Students

Abstract: This study explored baccalaureate students' perception of the characteristics of an effective clinical instructor utilizing the Whitehead Characteristics of Effective Clinical Instructor Rating Scale. The instrument is a 39 item 5 point Likert-type scale that measures, interpersonal relationships, personality traits, teaching practices, knowledge and experience, and evaluation procedures. This descriptive, cross-sectional study utilized a sample of 110randomly selected second and third year students from an ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…Such results were attributed to nursing students’ preference for nursing competence rather than the personal attributes of their teacher . Similar findings were noted in a study involving Hong Kong and Jamaican student nurses . Faculty ‘personal attributes’ were also identified as the least important nursing faculty characteristic among nursing students .…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…Such results were attributed to nursing students’ preference for nursing competence rather than the personal attributes of their teacher . Similar findings were noted in a study involving Hong Kong and Jamaican student nurses . Faculty ‘personal attributes’ were also identified as the least important nursing faculty characteristic among nursing students .…”
Section: Resultssupporting
confidence: 75%
“…In two separate studies conducted in the United States, American nursing students identified the availability, approachability and interpersonal skills of their nurse instructors as being the main characteristics of an effective clinical teacher (44,47). The same results were obtained in four studies conducted in Taiwan (24), Jordan (27), Jamaica (50) and Iran (42), respectively. In particular, the same domain of teaching behaviours (interpersonal skills) was rated as being the most important.…”
Section: Most Desirable Teaching Behaviours Of the Nursing Facultymentioning
confidence: 56%
See 3 more Smart Citations